Fast-ion transport and neutral beam current drive in ASDEX upgrade. (30th June 2015) - Geiger, B.; Weiland, M.; Jacobsen, A.S.; Rittich, D.; Dux, R.; Fischer, R.; Hopf, C.; Maraschek, M.; McDermott, R.M.; Nielsen, S.K.; Odstrcil, T.; Reich, M.; et al.
Abstract: The neutral beam current drive efficiency has been investigated in the ASDEX Upgrade tokamak by replacing on-axis neutral beams with tangential off-axis beams. A clear modification of the radial fast-ion profiles is observed with a fast-ion D-alpha diagnostic that measures centrally peaked profiles during on-axis injection and outwards shifted profiles during off-axis injection. Due to this change of the fast-ion population, a clear modification of the plasma current profile is predicted but not observed by a motional Stark effect diagnostic. The fast-ion transport caused by MHD activity has been studied in low collisionality discharges that exhibit strong modes. In particular due to sawtooth crashes, significant radial redistribution of co-rotating fast-ions is observed which can very well be described by the Kadomtsev model. In addition, first tomographic reconstructions of the central 2D fast-ion velocity space in the presence of sawtooth crashes allow the investigation of the pitch dependence of the mode-imposed redistribution: a stronger redistribution of mainly co-rotating fast ions is observed than of those with smaller pitch values.